2021
DOI: 10.32479/ijeep.11095
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Sustainability Disclosures in Oil and Gas Listed Companies in Nigeria

Abstract: This paper assesses the level of corporate sustainability disclosures in an environmentally-sensitive industry in Nigeria -the oil and gas industry. The paper aims to evaluate the extent of sustainability disclosure in the annual report's oil and gas industries. The study retrieves secondary data on sustainability disclosure for 10 years (2010 -2019) from eight oil and gas industries listed in the Nigerian stock exchange through a desktop approach and content analysis methodology. Content analysis of the susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In other words, social and environmental reports are pointless if they cannot be independently verified (Nwobu, 2017;Saleh et al, 2010a). Consistent with the LT, empirically, Nwobu et al (2021) established that oil and gas companies fully disclosed their community investment by legitimizing smokescreen ecological pollution on their annual reports.…”
Section: Assurance and Sustainability Initiativesmentioning
confidence: 82%
“…In other words, social and environmental reports are pointless if they cannot be independently verified (Nwobu, 2017;Saleh et al, 2010a). Consistent with the LT, empirically, Nwobu et al (2021) established that oil and gas companies fully disclosed their community investment by legitimizing smokescreen ecological pollution on their annual reports.…”
Section: Assurance and Sustainability Initiativesmentioning
confidence: 82%
“…Meanwhile, Michelon et al, (2021) and Diouf and Boiral (2017), observed that sustainability reporting in most developing countries is a mere management tool to impress the stakeholders, leading to low quality sustainability report incapable of presenting the accurate sustainability performance of a company's to report users. Similarly, Anwar and Malik (2020) (Ogbodo 2015;Onyali et al, (2015), drivers of sustainability reporting (Ikpor et al, 2022), extent of sustainability disclosures (Nwobu et al, (2021), influence of country governance factors and national culture on corporate sustainability practice (Ogundajo et al, 2022), and role of integrated accounting postulate on bridging stakeholders financial reporting expectation gap (Joshua et al, 2021). Evidently, there is lack of empirical evidence to determine the role of sustainability reporting practices in bridging stakeholder expectation gaps.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Studies on sustainability reporting in Nigeria have focused on such issues such as; determining the nexus between sustainability practices and competitive advantage of listed manufacturing companies in Nigeria , the nexus between sustainability reporting and firms value (Nwaigwe et al, 2021), factors affecting environmental disclosure practices of companies (Oyadonghan & Eze, 2013), effect of stakeholders' expectations on environmental accounting practices (Olaleye & Igbekoyi 2020), effectiveness of triple bottom line accounting disclosure practices (Ogbodo 2015;Onyali et al, (2015), drivers of sustainability reporting (Ikpor et al, 2022). Other studies include extent of sustainability disclosures in oil and gas listed companies in Nigeria (Nwobu et al, (2021), and role of integrated accounting postulate on bridging stakeholders financial reporting expectation gap (Joshua et al, 2021). The need for a comprehensive examination of whether sustainability reports can be used in bridging stakeholders expectation gaps in Nigeria has not been answered until now.…”
Section: Introductionmentioning
confidence: 99%
“…Performance management is a critical component of organizational and technical efficiency ( Nwobu et al., 2021 ). Businesses must find elements that boost employees’ performance to get the most out of them.…”
Section: Literature Reviewmentioning
confidence: 99%